Diabetes in Native Chicago : An Ethnography of Identity, Community, and Care - Pollak, Margaret (Book collections on Project MUSE., 2021)
"In Diabetes in Native Chicago, Margaret Pollak explores experiences, understandings, and care of diabetes in a Native urban community that is made up of individuals representing more than 100 tribes from across the United States and Canada"--